EFEKTIVITAS IMPLEMENTASI MEDIA PERMAINAN DIGITAL SEBAGAI INOVASI PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA GEN ALPHA - R. N. Azizah Andi Taweng; Andi Astriani; Andi Fiantika F; Marsyida; Maftuh Dzaki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the need for innovative learning approaches that align with the characteristics of Alpha generation students, who are highly familiar with digital technology. The use of digital game-based media in learning is considered a potential alternative to improve students’ learning outcomes. This study aims to analyze the effectiveness of implementing digital game-based learning media in improving the learning outcomes of third-grade students in the subject of Natural and Social Sciences (IPAS). The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The subjects consisted of 28 students. The research instrument was a learning outcome test administered before and after the treatment. Data analysis was conducted using the Shapiro-Wilk test for normality, the Wilcoxon Signed-Rank test for hypothesis testing, and the Normalized Gain (N-Gain) and effect size to measure the level of improvement and the strength of the effect. The results showed a significant difference between pretest and posttest scores (p < 0.001). The mean pretest score of 47.50 increased to 86.79 in the posttest, with an N-Gain value of 0.748, categorized as high. The effect size indicated a very strong effect, demonstrating that digital game-based media had a substantial impact on improving students’ learning outcomes. It can be concluded that digital game-based learning media is effective as an innovative approach to enhance the learning outcomes of Alpha generation students in IPAS.